Spokane's history of Skiing 1913-2018 : a project to benefit the Friends of Mt. Spokane State Park - Currie, Cris M. (Gray Dog Press, 2018)
For over 100 years, people in Spokane, Washington have been learning to ski, creating facilities for skiers, and putting on events that showcase the sport for spectators and the curious. While Spokane has not yet developed a national or even a statewide reputation as a destination ski town, many of its early promoters definitely had that goal in mind, and many today believe Spokane to be a relatively unknown jewel. Several small ski areas within Spokane County have come and gone, but Mount Spokane has consistently entertained skiers since the early 1930s. From back cover.